Pancasila dalam Pendidikan sebagai dasar pengembangan Ilmu dan Teknologi - faizah, siti zainab (Maliki Interdisciplinary Journal, 2026)
Pancasila functions as the foundation of the state as well as a moral guideline that directs the development of scientific knowledge in Indonesia. Education serves as the primary medium for applying the principles of Pancasila in the learning process, character building, and the creation of an ethical scientific culture. This paper explains the application of the values of each principle in teaching, curriculum design, and student behavior. The analysis shows that Pancasila plays an important role in shaping scientific knowledge that not only focuses on intellectual advancement but also prioritizes morality, humanity, unity, democracy, and justice. Through the implementation of these values, education in Indonesia is expected to produce a generation that is critical and innovative while still grounded in ethics and social responsibility. In addition, the integration of Pancasila in scientific development ensures that technological progress and research remain aligned with national identity and interests. In this way, education not only aims for academic achievement but also for character development and the cultivation of national awareness. The values of Pancasila serve as a reference to prevent the misuse of scientific knowledge and to encourage the wise use of technology in order to create a progressive, dignified, and just society.